Legal Protection of Intellectual Property in the Digital Era in Indonesia - Barmansyah, Alfi Syahrin; Indrawan, Chyndhyane Salsabila; Komalasari, Mutiara; Fajri, Muhamad Rifqy (JURNAL AKTA, 2025)
The advancement of digital technology has fundamentally transformed the processes of creating, distributing, and using intellectual works. While digitalization enhances accessibility and efficiency, it also significantly increases the risk of Intellectual Property Rights (IPR) infringements that occur on a large scale, at high speed, and across national borders. In Indonesia, these developments present serious challenges to the effectiveness of IPR legal protection, particularly in addressing violations within the rapidly evolving digital environment. This research seeks to assess the capacity of Indonesia’s IPR protection policies to respond to the demands of the digital era and to propose legal and policy recommendations aimed at strengthening the national IPR protection framework. The study employs normative legal research methods, utilizing statutory and conceptual approaches through a literature review of IPR legislation, legal doctrines, and academic writings related to digital technology. The findings reveal that although Indonesia has established a relatively comprehensive IPR regulatory system and has aligned it with international standards, existing regulations have not yet fully adapted to the unique nature of digital-era infringements. Persistent challenges remain in areas such as law enforcement effectiveness, the handling of electronic evidence, institutional coordination, and the regulation of cross-border IPR violations. The study concludes that enhancing IPR protection in Indonesia requires regulatory reforms that are responsive to technological advancements, improved capacity-building for law enforcement authorities, and increased public awareness of IPR law. Academically, this research contributes to the development of legal scholarship and provides valuable input for policymakers in strengthening IPR protection to ensure legal certainty and enhance national competitiveness.